La libertà del dilettante - Cocconi, Giulia (Venezia Arti)
Through the case of the amateur painter and engraver Gerolamo Imperiale, a Genoese patrician who, in the Parma of Ranuccio I Farnese, alternated university lectures at the Studium with attendance at the painters' workshops, the article intends to reflect on how amateurs were trained and their relationship with painters and the art market. Ubiquitous in seventeenth-century art literature, young members of the nobility who dabbled in painting, training alongside house painters or in the schools set up in the artists' studios, had the opportunity to engage in close contact with the work of their masters, but without being burdened by the professional constraints affecting collaborators and pupils, or by the impositions of patronage. With this in mind, we intend to examine the particular combinatorial freedom that Gerolamo Imperiale demonstrates in the invention engravings of his Parma years.